Simulated real-time controller for tuning algorithm using modified hill climbing approach - Ahmed, Ahmed Abdulelah (2014)
Many techniques and inventions in the field of automatic control keeps going forwards, especially that the introduction of modern computing provided a huge ground for innovation in this field. Intelligent control was one of the direct beneficiaries of the computer systems advancements. That led to new ways to tackle old problems like model inaccuracies and inconsistencies. Often, it is necessary to calibrate a certain parameters of a control system due to plant parameters fluctuation over time.In this research, an intelligent algorithmic tuning technique suitable for realtime system tuning based on hill climbing optimization algorithm and model reference adaptive control system (MRAC) technique is proposed. Although all adaptive control tuning methodologies depend partially or completely on online plant system identification, the proposed method uses only the model that is used to design the original controller, leading to simplified calculations that require neither high processing power nor long processing time, as opposed to identification techniques calculations. The main principle in the tuning process is to compare the output of the plant with a desired reference signal within an acceptable error margin. In order to investigate the ability of the proposed tuning method to deal with different system complexities, simulations of three different case studies were conducted. In each case study, different possibilities to generate the desired reference signal is discussed along with how much the complexity of the system would affect the end result. Also, in each case study a discussion contrasts the limitations and conditions needed to be identified to use the proposed method. The proposed design performed very well, improving overshoot and response speeds in example systems depending on reference response generation method. The results showed that using different methods to generate the reference response gives system designer flexibility over favouring a specific response characteristics or an overall decent response. The simulation results illustrates that the method schemes proposed in this study show a viable and versatile solution to deal with controller tuning for systems with model inaccuracies as well as controller real time calibration problem.